EFFECT OF PERMEABLE VESSEL CLOSURE AND GELLING AGENT ON REDUCTION OF HYPERHYDRICITY IN IN VITRO CULTURE OF CARNATION - Winarto, B.; Aziz, M.A.; Rashid, A.A.; Ismail, M.R. (Indonesian Journal of Agricultural Science, 2004)
Hyperhydricity, an abnormal morphological appearance and physiologicalfunction, is an important problem in carnation tissue culture. The problem causes premature flowering, high occurrence of abnormal shoots, difficulty in transferring hyperhydric plantlets to soil, and low survival rate of plantlets. High relative humidity and the water potential are considered as the key factors involved in the abnormality. Furthermore, permeable culture vessel and gelling agent were assured to be high potential treatment to eliminate it. Objective of this research was to reduceÂ  hyperhydricity in regenerants of carnation using different permeable vessel closures and gelling agents and to assess the multiplication andÂ  acclimatization abilities of recovered shoots. Experiment was arranged in randomized complete block design with four replications. First factor was different types of closure, i.e. cotton wool, plastic wrap, parafilm and aluminium foil, while second one was gelling agents, i.e. bacto agar, phytagel, swallow agar, and Type 900 agar. The recovered shoots were then multiplied, rooted, and acclimatized. The results showed that hyperhydricity was successfully reduced by applying permeable closure (cotton wool and plastic wrap) in combination with Type 900 agar. Thecombination of plastic wrap and Type 900 agar was the most appropriate treatment in reducing hyperhydricity and producing good quality shoots. The treatment reduced the problem down to 23% of total condition of hyperhydricity (100%) and increased leaf chlorophyll content from 0.0883 to 0.1288 mg mg-1. The plastic wrap was easily applied and cheaper material compared to cotton wool. The recovered shoots were able to produce 1-3 healthy axillary shoots and easily rooted on half-strength MS. The recovered plantlets were simply acclimatized with survival rate upto 100% on kossas peat + soil (1:1, v/v) and flowered 4-5 months after acclimatization with decreasing in number and size of flower.